USING MICROSOFT EXCEL IN RECAPITULATING STUDENT SCORES FOR PRIMARY TEACHERS - Andri Rahadyan; Indra Kurniawan; Rahman Abdillah (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2022)
The purpose of implementing the Community Prescription was to increase the knowledge and skills of teachers in SD N 1 and 2 Setu using Microsoft Excel to recapitulate student data and values so that this is a solution for teachers and admin staff. They no longer use manual methods. The implementation of this activity is carried out in three stages: preparation, performance, and evaluation. The implementation stage starts with the basics of using Microsoft Excel. At the preparation stage, the community service team was surveyed to determine the conditions and analyse the places to use. Next, the team prepares the material to be given in providing training to community service participants. This service activity involves presentations, lectures with questions and answers, and practice. While delivering the material, the community service team conducted a question-and-answered session with the participants, who were expected to interact with the servants and the participants. The last stage is the evaluation stage. The community service team gives the participants time to make examples of inputting data and student grades in the rankings.